Ship collision analysis : proceedings of the International Symposium on Advances in Ship Collision Analysis, Copenhagen, Denmark, 10-13 May 1998 /: proceedings of the International Symposium on Advances in Ship Collision Analysis, Copenhagen, Denmark, 10-13 May 1998. (1998) - Unknown
No abstract available